Distribuição e fontes de hidrocarbonetos policíclicos aromáticos em sedimentos da baía do Guajará, Pará - Brasil - MELLO, Leonardo Henriques (2020)
The coastal zone of Para is of paramount economic importance, considering that it is directly related to fishing activities, tourism and urban ocupation. Among the environments found in this region, the estuarine environment can be considered the most dynamic, as it is often subject to physical and hydrodynamic factors, which are responsible for the morphological and biogeochemical characterisitics. These allow environmental changes as well as potential social impacts, especially when related to pollution. The Polycyclic Aromatic Hydrocarbons (PAHs) are considered priority pollutants by environmental agencies because of the potential carcinogenic, teratogenic and mutagenic. Matrices such as soil and sediment are able to accumulate these compounds, being good indicators of contamination. Seen the importance of these hydrocarbons to understanding the resulting pollution in estuarine environments, the present work aimed to investigate the distribution and level of contamination of PAHs in sediments of the Guajará Bay, indicating their possible sources and classification them according to the main quality criteria sediment. Seven points were chosen, including the mouths of the drainage channels of Belém Metropolitan Region and reference areas without significant urbanization. The samples were analyzed by liquid chromatography high efficiency with diode array detection (HPLC-DAD), second method already optimized. The sum of the concentration of PAHs (ΣHPAs) ranged from 23.83 to 268.70 ng g-1, suggesting no impact our conditions of moderately impacted. The sample of "Furo do Maguari” showed the highest contamination in relation to the reference point (“Ilha das Onças”). Across the diagnostic ratios was possible to distinguish sources and origins of these contaminants. The low values for the ratios between the concentrations of PAHs of low molecular weight and high molecular weight PAHs (LMW/HMW) showed predominantly related to natural pyrolytic origin. However, the ratios between the concentrations of specific PAHs such as Fluoranthene / Pyreno and Fluoranthene / Fluoranthene + Pyrene indicated anthropogenic influence, related to fossil fuel sources. Moreover, it also became clear positive correlation between the content of total organic carbon (TOC), grain size and content of PAHs to the study area.